2019
DOI: 10.1038/s41598-019-41793-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological Study of Monkey Foveal Retina

Abstract: The fovea centralis, an anatomically concave pit located at the center of the macula, is avascular, hypoxic, and characteristic of stem-cell niches of other tissues. We hypothesized that in the fovea, undifferentiated retinal-stem-cell-like cells may exist, and that neurogenesis may occur. Hence, we performed an immunohistological study using cynomolgus monkey retinas. After preparing frozen tissue sections of the retina including the foveal pit, immunostaining was performed for glial fibrillary acidic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 86 publications
0
17
0
1
Order By: Relevance
“…The morphological and locational features of this inner retinal cavity on OCT images are consistent with the histologically known location of the Müller cell cone (MCC), and it is suggested that these cavities might be related to the MCC damage. The MCC is known to have no contact to synapses or neuronal elements other than the central cones and lateral process that extend to the deep capillary plexus at the border between the inner nuclear layer and the outer plexiform layer 6,7 . This could be the reason for the findings of the only inner retinal cyst without ELM disruption.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological and locational features of this inner retinal cavity on OCT images are consistent with the histologically known location of the Müller cell cone (MCC), and it is suggested that these cavities might be related to the MCC damage. The MCC is known to have no contact to synapses or neuronal elements other than the central cones and lateral process that extend to the deep capillary plexus at the border between the inner nuclear layer and the outer plexiform layer 6,7 . This could be the reason for the findings of the only inner retinal cyst without ELM disruption.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that it is difficult to attribute the improvement in VA and the restoration of the lamella structure of the fovea centralis simply to glial cell proliferation. In previous studies, we speculated the presence of neural stem cell-like cells with regenerative ability in the fovea centralis [15, 16], and reported the possible involvement of serine proteases such as chymase and tryptase in the vitreous body in the development of MH and ERM [1719]. Since chymase has an apoptotic effect and tryptase induces tissue fibrosis, we theorized that such serine proteases might be involved in the pathogenesis of MH and ERM.…”
Section: Discussionmentioning
confidence: 92%
“…However, several recent studies have indicated that retinal stem cells capable of differentiating into neurons are present in the adult primate retina [ 36 , 37 , 38 , 39 ]. Müller and RPE cells, as well as retinal precursor cells in the foveola and peripheral retinal margin, have been considered as candidates of adult primate retinal stem cells [ 35 , 36 , 37 , 38 , 39 , 40 ]. In this study, we assumed that the retinal lattice degeneration might have been caused by the inhibition of the regenerative potential of retinal stem cells, possibly transdifferentiated RPE cells.…”
Section: Discussionmentioning
confidence: 99%